MONITORING OF MOVEMENT OF OBJECTS USING GEOINFORMATION SYSTEMS - POPERESHNYAK, SVITLANA; VECHERKOVSKA, ANASTASIA; ZHYTKEVYCH, OLEKSANDR; ANTONENKO АRTEM (Herald of Khmelnytskyi National University. Technical sciences, 2023)
One of the parameters that allow you to identify the object of observation are its coordinates. In turn, the quality of identification - the probability of correctly recognizing the objects of observation - directly depends on the accuracy of determining its coordinates. In view of the growth in the number of observation objects and, accordingly, the sources of radio radiation, the density of their location in space increases, which leads to a constant increase in the requirements for the accuracy of the location of determination. This makes the task of developing and improving methods for determining the coordinates of observation objects urgent when creating geo-information systems. The purpose of the research is to create a system for monitoring moving objects based on geoinformation data. During the research and processing of their results, methods of digital and simulation modeling and software emulation of the work of algorithms were used. During the research, the principles of building geoinformation systems were analyzed and areas of their application were identified. The paper analyzes the technologies for determining the coordinates of moving objects for the construction of geoinformation systems. In the work, the methods of determining the coordinates of moving objects were investigated and a comparative analysis of the methods of determining the coordinates of moving objects based on GPS, Wi-Fi and ZigBee technology was carried out. The paper presents the advantages and disadvantages of the specified technologies for determining the coordinates of moving objects in geoinformation systems. As a result, the choice of software for developing a system for monitoring moving objects was justified. In the work, the method of determining the coordinates of moving objects was improved due to the combination of data from various coordinate determination technologies, which made it possible to increase accuracy. The developed software can be used to determine the coordinates of moving objects for the construction of geographic information systems.